Цифровий друк як засіб перенесення абрису на літорафську форму - Локатир, Б. І.; Цуца, Н. М. (ТОВ «Видавництво Ліра-К», 2025)
The report examines the use of digital printing as a modern method for transferring a contour drawing onto a lithographic plate. It analyzes the advantages of combining digital technologies with traditional lithographic techniques. The main stages of the technological process are described. Attention is drawn to the method’s precision, convenience, and potential. Its significance for the development of graphic art and education is emphasized.
Keywords: цифровий друк; абрис